Framing Analysis: Do Illegal Online Loans Have Fraud - Irwandi, Soni Agus; Shonhadji, Nanang (Universitas Swadaya Gunung Jati, 2023)
This study aims to examine how the framing of news illegal online loan fraud in online mass media which is then used as information to find out the causes of the fraudulent practices. The Pan and Kosicki framing analysis method, which was extended with the fraud hexagon theory, were used. The sites in this study were online mass media, particularly tribunnews.com and kompas.com, reporting cases of fraud committed by illegal online lending companies. The results of the framing analysis on the news published by Tribunnews.com show that illegal online lending companies have committed fraudulent practices to their customers and their existence is very disturbing to the public. Kompas.com uses a more preventive method by revealing the ways that the people should do to avoid these traps and fraud. The results of the analysis using the fraud hexagon theory show that fraudulent practices committed by illegal online lending companies are caused by pressure from capital owners, information technology capabilities owned, broad market opportunities, rationalization that people need fast funds, ego, and binding agreements as a form of collusion. The increasing role of the government in providing protection for the public in online transactions is an important implication of this research.